Pendidikan Kesehatan dengan Pendekatan Keluarga dalam Menurunkan Tingkat Merokok pada Remaja di Desa Hunuth Kota Ambon - Idham Soamole; Windarti Rumaolat; Sahrir Sillehu; Zulfikar Lating; Siti Rochmaedah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Smoking behavior among adolescents remains a major public health issue due to its high prevalence and potential long-term effects on physical, psychological, and social health. One key factor influencing adolescent behavior is the family environment. A family approach that incorporates effective communication, parental supervision, role modeling, emotional support, and consistent enforcement of rules is believed to significantly impact the prevention and reduction of smoking behavior in adolescents. This study aims to analyze the effect of a family approach on smoking behavior in adolescents. Adolescents who experience open communication, good supervision, and emotional support from their families tend to exhibit stronger self-control and are more likely to resist peer pressure to smoke. The findings suggest that an optimal family approach is crucial in shaping healthy behavior in adolescents and serves as an effective strategy in smoking prevention efforts. This approach not only helps in reducing smoking behavior but also fosters overall well-being by creating a supportive family environment. In conclusion, family involvement plays an essential role in promoting healthier behaviors in adolescents and preventing smoking, contributing significantly to public health improvement